(5 - 3/4 : 1/6) : 2/3 = 3/4
1) 3/4 : 1/6 = 3/4 · 6/1 = (3·3)/(2·1) = 9/2 = 4 1/2
2) 5 - 4 1/2 = 4 2/2 - 4 1/2 = 1/2
3) 1/2 : 2/3 = 1/2 · 3/2 = 3/4
ответ: 3/4 (или 0,75 в десятичных дробях).
Пошаговое объяснение:
(5-3/4:1/6):2/3
3/4÷1/6 = 3/4 * 6/1 = 9/2
5-9/2 = (10-9)/2 = 1/2
1/2 ÷ 2/3 = 1/2 * 3/2 = 3/4 = 0.75
(5 - 3/4 : 1/6) : 2/3 = 3/4
1) 3/4 : 1/6 = 3/4 · 6/1 = (3·3)/(2·1) = 9/2 = 4 1/2
2) 5 - 4 1/2 = 4 2/2 - 4 1/2 = 1/2
3) 1/2 : 2/3 = 1/2 · 3/2 = 3/4
ответ: 3/4 (или 0,75 в десятичных дробях).
Пошаговое объяснение:
(5-3/4:1/6):2/3
3/4÷1/6 = 3/4 * 6/1 = 9/2
5-9/2 = (10-9)/2 = 1/2
1/2 ÷ 2/3 = 1/2 * 3/2 = 3/4 = 0.75